Cerebral Palsy as a Challenge to Children's Language Acquisition: A Psycholinguistic Perspective - Idrus; Siti Hadija Alaydrus; Mohammad Bahrul Ulum; Usman Pakaya (Journal of Linguistica, 2025)
Cerebral palsy (CP) is a neurological disorder that can affect a child's motor and cognitive development, including language acquisition. From a psycholinguistic perspective, language acquisition in children with CP is a challenge in itself due to limitations in motor, sensory, and cognitive aspects that impact the ability to speak, understand, and produce language. This article discusses how neurological and environmental factors play a role in the language acquisition of children with CP as well as intervention strategies that can support their language development. With a psycholinguistic approach, this study examines various factors that influence language acquisition in children with CP, including the involvement of certain brain areas, communication adaptation, and the use of assistive technology. The results of the discussion show that a multidisciplinary approach involving speech therapy, early language stimulation, and social support can help children with CP develop their language skills.